The establishment, through action research, of an appropriate strategic ICT planning process for the South African Department of Defence as a diversified organisation - Lotriet, H.H. (Hugo H.) (University of Pretoria, 2013)
Thesis (PhD(IT))--University of Pretoria, 2008.